(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
The project results are discussed in six separate sections: project review; site formation; radiocarbon dating; site interpretations, physical archaeology of the sites and cultural archaeology. The project review considers the success of the methodology employed and the relative archaeological value of the various studies along with specific specialist recommendations. Section two deals with soil matrix, anthropic and non-soil natural components, processes of accumulation, loss of sediments, depositional rates and preservation conditions. Section three considers individual site chronologies and the calibrating of the marine reservoir effect. Section four presents a phased discussion for each of the sites. Section five covers structural and artefactual evidence. The final section looks at site economy, animal husbandry, landholdings. food storage and preparation, settlements and marginality.